Nasal Endoscopy Findings in Acute and Chronic Rhinosinusitis Patients - Stephanie Dharmaputri; Lina Lasminingrum; Yulia Sofiatin (Althea Medical Journal, 2017)
Background: According to European Position Paper on Rhinosinusitis and Nasal Polyps (EPOS) 2012, rhinosinusitis is diagnosed based on symptoms, nasal endoscopy, and CT scan. The CT scan is the gold standard to diagnose rhinosinusitis, but its high cost and lack of availability become the problems in Indonesia. Hence, nasal endoscopy is a choice to diagnose rhinosinusitis. This study was aimed to describe the findings of nasal endoscopyin in acute and chronic rhinosinusitis. Methods: This cross-sectional descriptive study was performed using medical record of acute and chronic rhinosinusitis patients. The samples were chosen with consecutive sampling. Inclusion criteria of this study were patients that underwent nasal endoscopy examination in Otorhinolaryngology–Head and Neck Surgery Clinic Dr. Hasan Sadikin General Hospital Bandung in 2014.The collected data were analyzed in the form of tables.Results: Among 138 patients, the number of female patients (55.1%) was higher than male patients. Majority of the patients (37.5%) were 25–44 years old. Majority of the chief complaint was nasal obstruction (48.6%). The patients with allergic history (48.6%) were higher than patients without allergic history (19.6%). According to nasal endoscopy results, nasal discharge and edema were found in most of the patients (68.8% and 63.0%), but nasal polyp was only found in 15.9% patients. Other findings, such as hypertrophy concha or nasal septum deviation, were also found on 87.7% patients. Conclusions: Most of the rhinosinusitis patients are found with at least one of the following results of nasal endoscopy, which are nasal discharge, edema, or nasal polyp.